CONTINUOUS-ROLE STRUCTURE OF PERSONALITY - Miroshnyk, Z. M. (Pedagogy of Higher and Secondary Education, 2022)
According foreign and modern native approaches we worked auf an entire role struc ture of a person. The structure of a person which we prepuce is divided info 3 levels : individual-psychological, interpersonal and social-cultured (professional).